Factors affecting the application of e-government (An Applied Study on the Ministry of Education Khartoum, Sudan): العوامل المؤثرة على تطبيق الحكومة الإلكترونية (دراسة تطبيقية على وزارة التربية والتعليم الخرطوم –السودان) - Nahla kamaleldeen Mohammed (Journal of engineering sciences and information technology, 2020)
This study is descriptive, aims to clarify the factors affecting the application of e-government in the Ministry of Education, Khartoum State, Sudan as infrastructure readiness and suitability, and identify the most important obstacles to their application and propose some solutions to those constraints. The study concluded that there is progress in the field of electronic applications that serve the application of e-government in the ministry through the application of many programs. The study concluded that the IT staff in the ministry does not have enough experience to manage the e-government systems, and activating the internal network is one of the most important components of the application of e-government in the ministry. The study concluded that a large number of employees and administrators have no desire to implement e-government systems. The study recommended the need to unify a basic database covering all aspects of education, and the need to establish an electronic training model for workers in the application of e-government in the ministry and the development of a model to re-engineering procedures in the ministry in line with the e-government Runes.